Can the principles of heterodox political economy explain its own re-emergence and development? - OHara, Phillip (Emerald Group Publishing Limited, 2008)
Purpose - This paper seeks to evaluate how some of the core general principles of heterodox political economy (HPE) can be applied to the issue of how HPE has managed to undergo resurgence and development over recent decades. Design/methodology/approach - Four major principles of heterodoxy are applied successively to this issue: historical specificty; contradiction; heterogeneous agents and groups; and circular and cumulative causation. Findings - These principles assist in comprehending how HPE is able to develop its own concepts, networks, publications, academic departments, teaching and policy-relevant material. Research limitations/implications - HPE has had considerable success in developing a conceptual apparatus, which helps to explain the emergence of much of its edifice being developed in academic and policy circles. The performance of HPE has been impressive. Practical implications - The conceptual apparatus of Heterodoxy can be applied to real world history over the past 40 years.Originality/value - This is the first time such a theme has been explored in the literature. Keywords - Economics, Political economy Paper type - Research paper.